(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The current study aims to assess the level of noise emission generated by the CNC milling machine Rover A.3.30 (Biesse, Italy). The change of the А-weighted sound pressure level (LpA) measured at the operator’s position at idle mode and during milling operations was investigated in relation to cutting tool rotation speed (n) and radial depth of cut (h) when processing particle boards, medium density fiberboards (MDF) and plywood. Sound pressure levels were determined using the precision digital noise meter CEL-620B1 (CASELLA, UK), taking into account the correction coefficients, accounting for the influence of background noises and sound field characteristics. The results show that at idle mode, without movement of the units along the x and y axes, the noise emission level was LpA = 72,6 dB(A), which is significantly below the upper safe limit of 85 dB(A) for eight hours of exposure. It was found that the A-weighted sound pressure level during cutting mode changed from 79,5 dB(A) to 85,6 dB(A), depending on the characteristics of the cutting process. The lowest level was registered when processing particle boards, followed by that of processing MDF and the highest level was measured for plywood. On the basis of the performed experiments, graphical dependencies representing the relationship between the different factors were compiled.